The Impact of ISO 14001 standards and non-financial reporting on company`s financial performance - Jovanović, Dejan; Vuković, Ivana; Todorović, Mirjana (Anali Ekonomskog fakulteta u Subotici, 2024)
Abstract: In today’s dynamic and complex business environment, companies increasingly understand how important care for the environment and social community is for the success of their operations. Тhere is an increasing number of companies that implement the ISO 14001 standard in their operations. The main research objective is to examine whether the implementation of the ISO 14001 standard and non-financial reporting affect the financial performance of companies. The research is conducted using induction and deduction methods, while the practical part focuses on statistical data analysis using non-parametric tests. The main conclusion of this research is that there is no statistically significant difference in financial performance, measured by the rate of return on equity and the rate of return on assets in the period from 2019 to 2021, among companies that have implemented the ISO 14001 standard and companies that have not implemented the standard, as well as companies that disclose and companies that do not disclose non-financial statements.